The Origin and Pathogenesis of Endometriosis - Wang, Yeh; Nicholes, Kristen; Shih, Ie-Ming (Annual review of pathology, 2020)
Recent molecular genetic findings on endometriosis and normal endometrium suggest a modified model in which circulating epithelial progenitor or stem cells intended to regenerate uterine endometrium after menstruation may become overreactive and trapped outside the uterus. These trapped epithelium-committed progenitor cells form nascent glands through clonal expansion and recruit polyclonal stromal cells, leading to the establishment of deep infiltrating endometriosis. Once formed, the ectopic tissue becomes subject to immune surveillance, resulting in chronic inflammation. The inflammatory response orchestrated by nuclear factor-κB signaling is exacerbated by aberrations in the estrogen receptor-β and progesterone receptor pathways, which are also affected by local inflammation, forming a dysregulated inflammation-hormonal loop. Glandular epithelium within endometriotic tissue harbors cancer-associated mutations that are frequently detected in endometriosis-related ovarian cancers. In this review, we summarize recent advances that have illuminated the origin and pathogenesis of endometriosis and have provided new avenues for research that promise to improve the early diagnosis and management of endometriosis.